The Influence of Education Level, Work Discipline, and Work Stress on Employee Productivity at CV.XYZ - Suryafni Limbong, Monita; Chandra Jaya, Rama (Journal of Accounting and Finance Management, 2024)
This study aims to determine the effect of education level, work discipline and work stress on employee productivity at CV. XYZ. The method used in this research is quantitative method with descriptive and verification approaches, the population used is 42 respondents of CV employees. XYZ by using saturated samples. Based on the results of the research conducted, it can be seen that the level of education has no effect on work productivity and the relationship between the level of education and productivity is 1.1. As well as Work Discipline affects Work Productivity by 3.5% and the relationship between work discipline and work productivity is 0.186 or 18.6%. And work stress affects productivity by 16.2% and the relationship between work stress and productivity is -0.402 or -40.2%. The results of the coefficient of determination analysis test show that the level of education, work discipline and work stress affect productivity by 40.5% while the remaining 59.5% is influenced by other factors not included in this study.